2018
DOI: 10.15252/emmm.201708736
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in intestinal epithelial O‐GlcNAcylation predisposes to gut inflammation

Abstract: Post‐translational modifications in intestinal epithelial cells (IECs) allow for precise control in intestinal homeostasis, the breakdown of which may precipitate the pathological damage and inflammation in inflammatory bowel disease. The O‐linked β‐N‐acetylglucosamine (O‐GlcNAc) modification on intracellular proteins controls diverse biological processes; however, its roles in intestinal homeostasis are still largely unexplored. Here, we found that levels of protein O‐GlcNAcylation and the expression of O‐Glc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 68 publications
4
61
0
4
Order By: Relevance
“…In addition, IFN-γ-induced STAT1 activation is required for the induced expression of Th1 lineage-determining transcription factor, T-bet [147]. Previous studies indicated that O-GlcNAcylated STAT1 enhanced the stability of phosphorylated STAT1 and its downstream signaling transduction [148,149]. Whether O-GlcNAcylation of STAT1 participates in the regulation of Th1 differentiation needs to be further determined.…”
Section: Role Of O-glcnacylation In T Cellsmentioning
confidence: 98%
“…In addition, IFN-γ-induced STAT1 activation is required for the induced expression of Th1 lineage-determining transcription factor, T-bet [147]. Previous studies indicated that O-GlcNAcylated STAT1 enhanced the stability of phosphorylated STAT1 and its downstream signaling transduction [148,149]. Whether O-GlcNAcylation of STAT1 participates in the regulation of Th1 differentiation needs to be further determined.…”
Section: Role Of O-glcnacylation In T Cellsmentioning
confidence: 98%
“…This is further supported by our data showing reduced pancreas weight and β-cell mass in adult OgtKO Panc mice after pancreas development. Hyper-O-GlcNAcylation is a general feature of evading apoptosis in cancer cells (Ferrer et al, 2014), and Ogt loss has been reported to regulate apoptosis in various cell types, including neurons (Wang et al, 2016) and intestinal epithelial cells (Zhao et al, 2018). Ogt deletion in pancreatic β-cells causes diabetes with remarked reduction in β-cell mass associated with increased apoptosis at P90 (Alejandro et al, 2015;Ida et al, 2017).…”
Section: Mechanisms Of Pancreatic Hypoplasia and Loss Of β-Cell Mass mentioning
confidence: 99%
“…Recent studies reported that levels of protein O-GlcNAcylation and the expression of O-GlcNAc transferase (OGT) were reduced in intestinal epithelial cells (IEC) of patients with UC and CD [108,109]. Similar to phosphorylation, OGT-modulated O-GlcNAcylation of Foxp3 is also critical for the lineage stability and effector function of Treg cells.…”
Section: Foxp3mentioning
confidence: 99%
“…Similar to phosphorylation, OGT-modulated O-GlcNAcylation of Foxp3 is also critical for the lineage stability and effector function of Treg cells. Mice with OGT deficiency either in IEC or Treg cells exhibited severe intestinal inflammation, indicating that OGT-modulated and Foxp3-based O-GlcNAcylation can regulate the development of colitis [108,110]. Pharmacological enhancement of intracellular O-GlcNAc levels promoted the increase in SOCS3 gene expression and the suppressive activity of human Treg cells [110].…”
Section: Foxp3mentioning
confidence: 99%
See 1 more Smart Citation